2012
DOI: 10.1007/s00417-012-2075-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum cortisol and testosterone levels in chronic central serous chorioretinopathy

Abstract: Serum cortisol and testosterone levels were within normal ranges and in patients with chronic CSC. The association between these hormones and chronic CSC might be weak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…[9] In the present study, 4% (1) with CSCR may have an impaired response to normal levels of serum cortisol and testosterone due to faulty choroidal/RPE response. [17] These findings are in conformation with the results of the present study. On the contrary, number of case reports of CSCR after systemic testosterone therapy shows indirect evidence of the role of testosterone in CSCR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[9] In the present study, 4% (1) with CSCR may have an impaired response to normal levels of serum cortisol and testosterone due to faulty choroidal/RPE response. [17] These findings are in conformation with the results of the present study. On the contrary, number of case reports of CSCR after systemic testosterone therapy shows indirect evidence of the role of testosterone in CSCR.…”
Section: Discussionsupporting
confidence: 92%
“…[28] suggested a weak association between cortisol and CSCR but this could be attributed to fairly low (six) number of subjects studied by them. [17] The visual acuity was significantly worse in the control group and was supposedly associated with more stress in the subjects which in turn should have led to increased blood cortisol but the presence of significantly high cortisol level in the CSCR patients, all the more strengthens the belief of glucocorticoids precipitating CSCR which could be either by their effect on the RPE or the choroidal vasculature. Also, increased cortisol acting via mineralocorticoid receptor (MR) may cause inappropriate expression of various channels viz.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact, several studies have shown that elevated serum testosterone is not universally present in cases of CSCR. 4,7,43 However, our experience suggests inquiring about the testosterone therapy in patients with CSCR, and in some cases, adjusting or stopping therapy may be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Serum cortisol levels were determined with the chemiluminescent immunassay method (IMMULITE® 2000 Xpi Immunoassay System, Siemens Healthcare Diagnostics). The normal range of reference serum cortisol level was determined as between five and 25 μg/dl …”
Section: Methodsmentioning
confidence: 99%